Contemporary surgical management of skull base chordomas—Anatomical reflections on a single center experience retrospective case series. Issue 3 (7th February 2022) - Spiessberger, Alexander; Dogra, Siddhant; Golub, Danielle; Grueter, Basil; Nasim, Mansoor; Schneider, Steven; Moriggl, Bernhard; Dehdashti, Amir R.; Schulder, Michael
Abstract: Chordoma, a rare, locally aggressive tumor can affect the central skull base, usually centered at the midline. Complete surgical resection remains mainstay of therapy in case of primary as well as recurrent tumors. Owing to their secluded location, surgical resection of skull base chordomas remains a challenge, even though the recent advancement of endoscopic endonasal approaches has had a significant positive impact on the management of these patients. Endoscopic endonasal approaches have been shown to significantly reduce surgical morbidity when compared to traditional open approaches; however, the classical endoscopic transclival midline approach fails to sufficiently expose parts of many skull base chordomas. More recent refinements of the technique, such as the interdural pituitary transposition and posterior clinoidectomy, the transpterygoid plate approach and the transcondylar far medial approach enable the surgeon the increase the resection rate in these patients. This retrospective case series focuses on anatomical aspects in the surgical management of patients with skull base chordomas. We outline the surgical anatomy of contemporary endoscopic approaches to the skull base based intraoperative illustrations as well as pre‐ and postoperative 3D reconstructed CT and MR images if our patients. This article should help the clinical choose the most appropriate approach and be aware of relevant anatomy as well as potential shortcomings of a given approach.